Sex Effect on The Telomer Length, Elemental Composition, and Phytochemical Content of Highland Papaya (Vasconcellea pubescens A.DC.) Leaves - Laily, A. N.; Daryono, B. S.; Purwantoro, A.; Purnomo, Purnomo (2023)
Highland papaya (Vasconcellea pubescens A.DC.) is a monoecious and dioecious plant with female and male organs. In Indonesia, three sexes of highland papaya exist with different telomere lengths, which protect chromosomes and deoxyribonucleic acid (DNA) from damage. Therefore, the purposeful study aimed to determine the telomere length, elemental composition, and phytochemical content of highland papaya leaves belonging to their different sexes. The telomere length observed and studied in said leaves (female, male, and monoecious) used the polymerase chain reaction (PCR) procedure. A scanning electron microscopy (SEM) analysis provided a more detailed material of leaves, while an energy dispersive X-Ray (EDX) helped observe elemental composition. Phytochemical content analysis ran by histochemical analysis. The results showed that the telomere lengths of young female, male, and monoecious leaves differed at 381, 391, and 396.66, respectively. According to the SEM analysis, nonsignificant differences occurred in the leaf surface of the three sexes of highland papaya leaves. Observation with EDX showed that sodium (1.98%) surfaced in female plant leaves; however, sodium and chlorine did not show in male plants. Monoecious leaves had sodium and chlorine at 0.88% and 0.28%, respectively. The histochemical analysis provided an overview of the distribution of flavonoids and tannins in young leaves of highland papaya. A discovery also noted the existence of both compounds in the adaxial and abaxial epidermis, mesophyll, xylem, phloem, sheath parenchyma, secretory cavities, and trichomes. The study concluded that sex affects telomere length, elemental composition, and the phytochemical content of highland papaya leaves. The study suggests that knowing the highland papaya’s sex is vital in plant breeding and genetics and could help improve plant health and productivity.